2022
DOI: 10.3390/healthcare10030415
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Launch and the Deployment of Telemedicine in Italy during the COVID-19 Pandemic

Abstract: Telemedicine is making an important contribution to the fight against the COVID-19 pandemic and to supporting the health domain. Its use has registered initial problems with often-patchy practise. The objective of this study was to analyze the launch and deployment of telemedicine in Italy through a narrative review. The narrative review faced two points of view: (a) the first point of view revised the institutional initiatives of the Italian government developed to promote the use of telemedicine; (b) the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Almost in all world regions, COVID-19 necessitated wearing facemasks to the general population, at least between 2020 and 2022 [ 1 , 4 ]. However, wearing facemasks has not been, and never would be, a uniform experience across nations due to cultural, gender, social, economic, and geopolitical forces [ 4 , 5 ]. Indeed, the COVID-19 pandemic has exposed and exacerbated multiple strands of inequalities worldwide [ 6 , 7 ], including in Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…Almost in all world regions, COVID-19 necessitated wearing facemasks to the general population, at least between 2020 and 2022 [ 1 , 4 ]. However, wearing facemasks has not been, and never would be, a uniform experience across nations due to cultural, gender, social, economic, and geopolitical forces [ 4 , 5 ]. Indeed, the COVID-19 pandemic has exposed and exacerbated multiple strands of inequalities worldwide [ 6 , 7 ], including in Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…The first , TD, inherits the problems of telemedicine and e-Health . These problems, such as their regulation, was only partially and patchily overcome during the COVID-19 pandemic [ 61 , 62 ]. The second , mHealth , has a very short history in terms of its connection to and integration with digital health imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review of the deployment of telemedicine in Italy during the COVID-19 pandemic revealed similar phenomena as experienced by users in Poland [ 34 ]. The authors of the review reported initial disorientation in the use of telemedicine preceding the preparation of recommendations for its use, an expansion of the telemedicine boundaries, and its high acceptance in the population.…”
Section: Discussionmentioning
confidence: 99%